Towards Next-Generation Deoxy Oligosaccharide Synthesis - Yalamanchili, Subbarao. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Chemistry.; Advisor: Clay Bennett.; Committee: Nicola Pohl, Krishna Kumar, and Samuel Thomas.; Keywords: Chemistry, and Organic chemistry.